Test standard, test artificial teacher, and condition test - Atikah Sri Wahyuni; Arinah Sabilulhaq; Syafina Nur isnaini; Ferlinda Nur Milayniawati; Yayan Sudrajat (Journal of Instructional Development, Innovation, and Evaluation, 2022)
This article aims to determine the differences between standardized tests, artificial teacher tests, and condition tests. Standardized tests are usually carried out by schools when schools carry out tests simultaneously at the sub-district level and at the national level. Meanwhile, teacher-made tests are carried out when teachers want to know the competencies possessed by students after learning. Keywords: standardized test, teacher-made test, and condition test